Hydrogeochemistry and quality assessment of groundwater in Jinghui canal irrigation district of China. Issue 9 (20th October 2020) - Zhang, Yan; Xiong, Yuqing; Chao, Yang; Fan, Ruirui; Ren, Feier; Xu, Bin; Liu, Zhao
Abstract: This study was carried out to investigate the hydrogeochemical characteristics, processes, and factors that control the groundwater chemistry in Jinghui canal irrigation district of China. Water quality was assessed by comparing with the Chinese national guidelines and World Health Organization (WHO) guidelines for drinking and irrigation. Impacts of Cr 6+ on human health were also quantified using the health risk assessment model. The results show that groundwater in the study area is brackish, hard and slightly alkaline. The groundwater quality is generally very poor with excessive Na +, SO4 2−, Cl −, total dissolved solids, and total hardness in most samples. Of the groundwater samples, 72.3% are unsuitable for drinking with excessive NO3 − -N comparing the WHO guidelines. The non-carcinogenic risks caused by Cr 6+ through drinking-water intake are low and acceptable for children and adults in most parts of the study area, while, both children and adults face unacceptable carcinogenic risks of Cr 6+ in the whole study area. Over 80% of the sampling sites are not permissible to irrigate by groundwater due to the alkalinity hazard. Long-term groundwater irrigation in the study area will result in the formation of saline, alkaline soil and the decreasing of crop yield. The results of this study may help to set up the suitable management strategies to guarantee water supply and health safety for local residents.